Coordinated operation approach for heat and electricity integrated energy systems - Vinod, Ashwin (Nanyang Technological University, 2023)
The increasing demand for energy and the need for reducing greenhouse gas emissions have led to the development of integrated energy systems that combine different energy sources and technologies. Among these, heat and electricity-integrated energy systems (HE-IES) have emerged as a promising solution for providing a sustainable and efficient energy supply. To optimize the performance of HE-IES, a coordinated operation approach is essential. This approach aims to balance the demand and supply of both heat and electricity, considering the dynamic interactions between the different components of the system. A coordinated operation strategy can improve the system's efficiency, reduce its operating costs, and enhance its reliability. The objective of this final year project is to explore the drivers and essential factors behind the uncertain net electrical load and outdoor temperature for the purpose of ensuring both the safety of HE-IES operation and the thermal comfort of end-users. To evaluate the effectiveness of the model, computer-based simulations are conducted.